Structural Misalignment - Coser, João Victor (Revista do Colóquio, 2021)
In the series “Structural Misalignment” (2020), I present a set of eight images and a video performance. The photographs were organized into triptychs and diptychs, composing a game of relationships between body, gesture and matter. In the performance, my body moves between positions of submission and power, crossed by a red line that dresses and covers me, tensioning the limits between interior and exterior. This line, a pulsating element, stitches together looks, body, flesh and blood, establishing a circle of gestures and confrontations.